Association of plant and animal protein intake with sleep quality and quality of life in hemodialysis patients: a multicenter cross-sectional study - Jafari Maskouni, Saber; Bavi Behbahani, Hossein; Alipour, Meysam; Zare Javid, Ahmad; Fayazfar, Fatemeh; Tofighzadeh, Pardis; Shokri, Shiva; Keramatzadeh, Sara; Soltaniyan Dehkordi, Haleh; Sharifat, Morteza; Babajafari Esfandabad, Siavash; Shayanpour, Shokouh (Frontiers in Nutrition, 2024)
The current study aimed to evaluate the association between the intake of plantbased protein, animal-based protein, total protein, and the ratio of plant to animal protein with sleep quality and quality of life in patients undergoing hemodialysis.In this cross-sectional study, 479 adult patients undergoing dialysis for a minimum of three months were included. The dietary intake was calculated using information from a validated 168-item semi-quantitative food frequency questionnaire. Quality of life (QOL) was assessed using the Kidney Disease Quality of Life Short Form (KDQOL-SF 1.3). and the Pittsburgh Sleep Quality Index (PSQI) was used to assess sleep quality.Results: In this study, the mean age of the participants was 58.18 years (± 14.25 years), with the majority being male (58.2%). After adjusting for potential confounders, significant positive associations were observed between total protein intake (β = 0.12, p = 0.03) and quality of life (QOL). Conversely, there were significant negative associations between the ratio of plant to animal protein intake (β = -0.94, p < 0.01) and QOL. Furthermore, significant negative associations were found between total protein intake (β = -0.02, p < 0.05) and animal protein intake (β = -0.19, p < 0.05) with poor sleep quality. Additionally, there were significant positive associations between the ratio of plant to animal protein intake (β = 0.188, p < 0.05) and poor sleep quality.Increased consumption of animal protein is associated with improved sleep quality and Quality of Life (QOL) in patients undergoing hemodialysis (HD). Further research, especially prospective studies, is required to confirm these associations.